Role of Technology in agriculture - Yadav, Kamlesh; Yadav, Vikas; Yadav, Prakash (Indian Farming, 2017)
As with any other crisis of our time, world hunger and malnutrition will require the efforts of all stakeholders. Through increased collaboration and partnerships, the global resources, expertise and tools can be collectively put to use. The Green Revolution demonstrated the potential of science to bring countries from famine to surplus of food. The world must again embrace collective innovation to achieve global food and nutritional security. With support of innovative solutions to farmers, including agricultural biotechnology, global food demand can be met in the future.